Smart Medical System for Trusted LoRaWAN Server - Gokulachandar, Adhikesavan; Shanmugam, KannanShanmugam; Vijayakumar, Shanmugam; Sugumaran, Subramanian; Senthil , Tamilselvan; Srinivasulu, Arigila; Lakshmi, Kalavagunta (Journal of Health Informatics in Africa, 2025)
leading tech of LoRaWAN in Smart Medical System (SMS) measures the human health parameters with no laboratory diagnosis. The system uses an ESP32 microcontroller and bio-sensors to examine the human physiological conditions based on environmental factors using low power components but provides a seamless experience with long-range communication modules (LoRa). Monitored data is centralized in a server that can be accessed securely from remote place. The main goal of this paper is to implement the patient’s health records maintenance with end-to-end encrypted data using consensus algorithms. An Authorized person only accesses encrypted data with the private key through decentralization. Simultaneously, the proposed system introduces an efficient method to get alert messages from the patient that enables sharing the predicted data in real-time to the caretaker and hospital doctor.